2002
DOI: 10.1136/bjo.86.10.1143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhalation of different mixtures of O2 and CO2 on retinal blood flow

Abstract: Aim: To determine the effects of various mixtures of O 2 and CO 2 on retinal blood flow in healthy subjects. Methods: A randomised, double masked, four way crossover trial was carried out in 12 healthy male non-smoking subjects. Gas mixtures (100% O 2 , 97.5% O 2 + 2.5% CO 2 , 95% O 2 + 5% CO 2 , and 92% O 2 + 8% CO 2 ) were administered for 10 minutes each. Two non-invasive methods were used: laser Doppler velocimetry (LDV) for measurement of retinal blood velocity and fundus imaging with the Zeiss retinal ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
66
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 16 publications
6
66
1
1
Order By: Relevance
“…Retinal blood flow varies inversely with arterial PO 2 to maintain retinal oxygenation at a relatively constant level (25,51) and also varies directly with arterial PCO 2 (34). Numerous studies have investigated retinal vascular reactivity using a hyperoxic stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retinal blood flow varies inversely with arterial PO 2 to maintain retinal oxygenation at a relatively constant level (25,51) and also varies directly with arterial PCO 2 (34). Numerous studies have investigated retinal vascular reactivity using a hyperoxic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…In three previously published studies (22,24,34), researchers have investigated the time course of the changes in diameter or velocity using a hyperoxic stimulus (referred to in this report as response time and response lag). To the best of our knowledge, this is the first time that the response characteristics of arteriolar diameter and blood velocity have been simultaneously quantified due to hyperoxic provocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show a reduction of 50 to 60% in retinal blood flow, which is closer to the values obtained in humans. [41][42][43][44][45][46] Studying the response of retinal blood flow to hyperoxia is interesting, because it has been shown to be disturbed early in diabetes. 47 However, the mechanisms which lead to this reduced vasoconstrictor response to hyperoxia are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The autoregulating ability of the retinal blood vessels has been reported previously. [7][8][9][10][11][12][13][14][15] Several studies have demonstrated changes in retinal vessel diameter, velocity, and flow to various provocative stimuli, such as carbon dioxide (CO 2 ), O 2 and flicker in healthy 12,16,17 and diseased cohorts. [18][19][20][21] Hypoxia, a decrease in O 2 concentration, has been shown to vasodilate the retinal vessels.…”
mentioning
confidence: 99%